Hospital design in tropical Malaysia - towards a green agenda - Mohd Nawawi, Norwina; Sapian, Abdul Razak; Abdul Majid, Noor Hanita; Aripin, Srazali (TESIS Inter University Research Centre System Technology for Social and Healthcare Facilities. University of Florence, 2013)
‘Sustainability’ as a terminology, is a broad concept and a requirement in building designs with a tendency of being abuse through trendy and over commercialisation. In the arena of hospital design, new is usually associated to being modern and therefore, green. In the quest of getting to know the “tree” from “the forest” from among the hundreds of existing hospitals, ranged from colonial, early independence to the new hospital designs, a yardstick, to measure those that is actually “green” and “sustainable” need to be set. This study intends to provide a qualitative definition and provide recommended criteria of a green hospital designs in the context of tropical climate of Malaysia and its people. A qualitative method of approach through case studies of hospital designs from pre-colonial to the present were made. Aspects studied include the physical architecture that significantly affect health i.e. the building configuration, form, space quality, material use and culture. Findings indicated that there is a variety of degree and factors to the implementation of the green qualities in all the designs. The range includes intuitive and regulatory approach to green considerations in the design. Conditions of the site, cost, construction time, planning time, expertise, experience and procurement methods are among the constraints where compromises had to be made as a priority. Significance of the findings will contribute to the qualitative criteria for healthcare building Green requirement especially for tropical climate of Malaysia.